Caregivers' perception of and experience with variants of uncertain significance from whole exome sequencing for children with undiagnosed conditions. Issue 2 (24th January 2019) - Li, Xin; Nusbaum, Rachel; Smith‐Hicks, Constance; Jamal, Leila; Dixon, Shannan; Mahida, Sonal
Abstract: Despite its promising diagnostic yield, whole exome sequencing (WES) frequently introduces variant(s) of uncertain significance (VUS), which have been speculated to cause parental stress and anxiety. This study aimed to explore the psychosocial impact of receiving a VUS from pediatric WES on caregivers and to identify implications for clinical practice. Fourteen telephone interviews were conducted with parents or legal guardians who received VUS results from their child's WES to assess their understanding of the result, affective responses, perceived impact, and adaptation. Our content analysis showed that most participants had a good understanding of the purpose of the test and the majority of them recalled the result category. Most participants deemed the result had no impact thus far on their perception of their child's condition. However, one participant reported feelings of fear related to the VUS. Most participants experienced a range of emotions from receiving the result. The majority of participants reported that this result did not significantly alter their child's care or their ability to take care of their child, and three participants reported empowerment. Additionally, several participants expressed an interest in research studies and peer support groups dedicated to families with a VUS identified on WES. Our study elicited new information about the psychosocial impact of receiving a VUS from WES. This insight may help to guide pre‐ and post‐WES counseling in the future.